Gender in law under and after state socialism: the example of the Czech Republic - Havelkova, B (2013)
The thesis examines the expressions and origins of negative attitudes to gender equality in the Czech Republic, which have been noticeable especially in the process of implementation of the EU sex equality acquis. It asks whether and how they can be explained with reference to socio-legal developments that started during Czechoslovakia’s State Socialist past, but are still relevant today. In order to answer these research questions, the thesis examines how gender equality has been regulated through law and how it has been understood by law-makers, judges and legal scholars in Czechoslovakia and the Czech Republic during State Socialism (1948-1989) and Transition (1989-today). The thesis examines legal developments in gender-relevant areas, most importantly in antidiscrimination law. It also excavates the underlying, sometimes hidden, but crucial understandings of key concepts such as ‘women’, ‘gender’, ‘equality’, ‘discrimination’ and ‘rights’. The thesis argues that while formal legal guarantees for women have largely been satisfactory in the Czech Republic by international standards, the way these formal legal guarantees are understood, interpreted and applied has not been gender-progressive. It argues that the reasons for this are: (i) entrenched patriarchal ideas about women’s appropriate role both in private and public life; (ii) a failure to understand gender as a social construct and to recognize gender order as a pervasive social structure; (iii) an inadequate conceptualization of equality and a refusal to combat sex discrimination; and (iv) a limited understanding of the role of law and of rights in the shaping of social relations. It argues that these understandings have been considerably path-dependent on State Socialism, be it through a rejection of anything perceived as State Socialist (which has harmed redistributive policies), as well as through the mostly unconscious retention of ideas or their absence (which has led to a blindness to the cultural aspects of patriarchy).